Exertional heat stroke in a marathon runner with extensive healed deep burns: a case report - Seth, Puneet (Springer, 2011)
Exertional heat illness typically occurs over hours in younger athletic patients or military recruits who exercise at elevated temperatures for a sufficient period of time to cause the rate of heat production to exceed the capacity of the body to dissipate heat. Since the physiological response to exercise includes cutaneous vasodilation and sweating, any limitation of such a response can cause rapid hyperthermia and thus heat stroke. One such condition is extensive burns healed by cicatrisation of the skin where the scar and grafted skin surface do not have functional sweat glands and are unable to lose heat in response to high temperatures. The authors report one unique case of a female marathon runner with exertional heat stroke who had recovered from deep second and third degree burns over approximately 50% of her body a few years ago.